Differences in external load among indoor and beach volleyball players during elite matches - Hank, Mikulas; Cabell, Lee; Zahalka, Frantisek; Miřátský, Petr; Cabrnoch, Bohuslav; Mala, Lucia; Maly, Tomas (PeerJ, 2024)
The aim of this cross-sectional study was to examine relationships of external load variables between beach and indoor volleyball amongst individual positions on the team. The movements of eight beach and fourteen indoor female volleyball players were recorded during elite playoff matches; in total, 2,336 three-dimensional trajectories were analyzed. Time-outs and intervals between rallies or sets were excluded from active play time. In both beach and indoor volleyball, 80% of rallies lasted up to 10 s, and players covered 4.5 to 10 m of court during 60% of rally play. Differences in dependent variables of external load were found between independent variables of sports and player positions (p < 0.05). The distance covered in beach volleyball rallies and Player Load™ parameters was significantly higher by up to 23%. The unstable court surface with sand in beach volleyball elevated explosive Player Load™ (accelerations in all three orthogonal planes of motion higher than 3.5 m/s3) in beach volleyball players compared to those of players on stable flooring in indoor. While beach volleyball blocker and defender positions showed no significant difference in parameters between each other, they differed in all parameters when compared to player positions in indoor volleyball. Indoor blocker and libero reached higher loads than setter, outside and opposite positions in various parameters. Factors that influence external load include the larger relative court areas covered by each player in beach volleyball, complexity of players' roles, and game strategy. This data adds to the knowledge of elite match demands in female volleyball. Specified agility-drill distances and times are essential for training optimization and must be supported by scientific observation. Researchers, coaches, and conditioning specialists should find this helpful for achieving a higher degree of training regulation.
Keywords: Match performance; Conditioning, Operant; Explosive Agents; Female; Motion analysis; Movement distance; Volleyball; ženské pohlaví; průřezové studie; volejbal; lidé; operantní podmiňování; Female athlete; Cross-Sectional Studies; Acceleration; Sand surface; zrychlení; výbušné látky; Player load; Humans